ASSESSMENT OF DUST AND AEROSOL POLLUTION IN THE ZONE OF INFLUENCE OF THE CEMENT PLANT BASED ON THE STUDY OF SNOW COVER (NOVOSIBIRSK REGION) - Darya A. Volodina; Anna V. Talovskaya; Egor G. Yazikov; Anna U. Devyatova; Alexey V. Edelev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
The relevance of the research. Air pollution is an important and urgent problem of our time. One of the main sources of particulate matter is the construction industry. Solid particles enter the atmospheric air as a result of the extraction, transportation and grinding of raw materials, clinker firing, grinding and transportation of cement. In this regard, the environmental assessment of dust and aerosol pollution of atmospheric air in the areas where cement plants are located is relevant. Purpose: to assess the state of atmospheric air in the vicinity of the cement plant based on the study of dust load, the levels of accumulation of chemical elements and the forms of their presence in the composition of solid particles settled in the snow cover in the vicinity of the cement plant in Iskitim. Objects: the solid phase of the snow cover containing dust and aerosol particles deposited from the atmospheric air into the snow cover in the area of the cement plant. Methods: atmogeochemical method, including the selection and preparation of snow cover samples to obtain a solid phase of snow cover; analytical methods for studying samples: inductively coupled plasma mass spectrometry, instrumental neutron activation analysis, X-ray phase method, scanning electron microscopy; methods of statistical processing of results in the software «STATISTICA 8»; ecological and geochemical analysis of data by calculating indicators – dust load (Pn), concentration coefficient (Kc), total pollution index (Zspz), cartographic presentation of the results in Surfer 11 and CorelDraw X7 software, raw materials for cement production (limestone, clay, slag, pyrite cinders). Results.The levels of dust load in the vicinity of the cement plant are in a wide range (from 57 to 1028 mg/(m2∙day) with an average value of 318 and a background of 7 mg/(m2∙day). Dust pollution ranges from low to very high level. The levels of dust load decrease from 436 to 78 mg/(m2∙day) in the north-north-west direction at a distance of 0,6 to 2,8 km from the plant. The near zone of influence (up to 500 m) – 1028 mg/(m2∙day), as well as in the area of the open pit where the main raw materials are mined – 932 mg/(m2∙day). The mineral composition of the solid phase of the snow cover is represented by minerals raw materials – calcite (CaCO3) – 82,1 %, quartz (SiO2) – 4,4 %, magnesite (MgCO3) – 7,6 %, cement clinker minerals – brownmillerite (Ca2(Al, Fe)2O5) and hatrurite (Ca3(SiO4)O)) – 6,4 and 26,6 %, respectively. In the solid phase of the snow cover, microparticles of calcium and iron oxides, as well as microparticles of aluminosilicate composition with sizes from 2,7 to 64,5 μm, were isolated. The technogenic geochemical specialization of the solid phase of the snow cover is characterized by elevated levels of accumulation of Ca (14–23 times higher than the background), Zn, Sr, Sb, Tb, Yb, La, Sm, U (2–7 times higher than the background), which form a low pollution level. The distribution of Ca and dust load with distance from the boundaries of the plant in the northwest direction are similar. The maximum levels of dust load (1028 mg/(m2∙day)) and Ca accumulation (24 %) in the solid phase of the snow cover were determined at a distance of 0,5 km, and as the distance from the plant boundaries (from 0,5 to 2,8 km), there is a decrease in the level of dust load by an average of 7 to 13 times (140–78 mg/(m2∙day)) and Ca accumulation by 1,5 times (16–17 %). Trace elements-indicators (Cr, Sb, Zn), which are defined in the reference book of the best available technologies as specific in the composition of cement production emissions, in the solid phase of the snow cover exceed background levels from 2 to 7 times. The solid phase of the snow cover is characterized by geochemical associations Zn-Cr, As-Ta, Yb-U-Sb, Tb-Ba, Th-Na, Fe-La. There are correlations between trace elements-indicators (Ca, Ba, Cr, As, Fe, Sb, Zn), characteristic of cement production emissions, with rare earth and radioactive (U, Th) chemical elements. This fact may indicate a single source of these elements (with positive correlations), and also reflect the difference in the composition of corrective additives for cement production and different forms of presence of chemical elements in the composition of solid particles in the vicinity of the cement plant (with negative correlations). The identified geochemical associations with a high degree of probability reflect the geochemical specialization of the raw materials used, corrective and mineral technological additives for cement production.